Webblog-Based Flipped Classroom: The Feasibility to Support 4C’s in the Content and Language Integrated Learning (CLIL) - Rohmah, Ima Isnaini Taufiqur; Nurdianingsih, Fitri; Anggraeni, Sherly Aisyia (FKIP Universitas Lampung, 2024)
Abstract: Weblog-Based Flipped Classroom: The Feasibility to Support 4C’s in the Content and Language Integrated Learning (CLIL). Objectives of the study were to analyze the feasibility of using weblogs based flipped classroom learning and how feasible to support the development of 4Cs in CLIL. Methods: using qualitative case study method, the data was collected through observations, semi-structured interviews and questionnaire. The data analyzed descriptively and to ensure the validity of the qualitative data, triangulation technique was carried out by analyzing and comparing the results of interviews and questionnaires simultaneously. Findings: the findings show that the use of weblogs in flipped class design in CLIL classes is feasible and it also perceived positively to support the 4C’s of CLIL. Conclusion: it is concludes that technology-based learning innovations have a big influence on the learning atmosphere and student learning motivation. Further research on how effective the use of weblog based flipped classroom developing the 4Cs in CLIL needs to be done to give contribution to the development of CLIL studies. Keywords: CLIL, feasibility, flipped classroom, weblog.DOI: http://dx.doi.org/10.23960/jpp.v14.i1.202448